Randomized stress-testing of link-time optimizers - Le, Vu; Sun, Chengnian; Su, Zhendong (2015 International Symposium on Software Testing and Analysis, 2015)
Link-time optimization (LTO) is an increasingly important and adopted modern optimization technology. It is currently supported by many production compilers, including GCC, LLVM, and Microsoft Visual C/C++. Despite its complexity, but because it is more recent, LTO is relatively less tested compared to the more mature, traditional optimizations. To evaluate and help improve the quality of LTO, we present the first extensive effort to stress-test the LTO components of GCC and LLVM, the two most widely-used production C compilers. In 11 months, we have discovered and reported 37 bugs (12 in GCC; 25 in LLVM). Developers have confirmed 21 of our bugs, and fixed 11 of them. Our core technique is differential testing and realized in the tool Proteus. We leverage existing compiler testing tools (Csmith and Orion) to generate single-file test programs and address two important challenges specific for LTO testing. First, to thoroughly exercise LTO, Proteus automatically transforms a single-file program into multiple compilation units and stochastically assigns each an optimization level. Second, for effective bug reporting, we develop a practical mechanism to reduce LTO bugs involving multiple files. Our results clearly demonstrate Proteus’s utility; we plan to make ours a continuous effort in validating link-time optimizers.